IL-21 plays an important role in modulating "Th17-Treg" cell axis in leprosy Type 1 reactions. (April 2022) - Saini, Chaman; Sapra, Leena; Bhardwaj, Asha; Tarique, Mohd.; Sharma, Alpana; Khanna, Neena; Ramesh, V.; Puri, Poonam; Srivastava, Rupesh K.
Highlights: The present study strongly suggests that IL-21 plays a pathogenic role in Type 1 leprosy reactions. IL-21 secretion in T1R is directly correlated with Th17 cells markers but not with regulatory Tregs markers. Recombinant IL-21 enhances inflammatory immune response in leprosy Type 1 reactions. Th17-Tregs cell balance could thus be therapeutically targeted in the management of T1R in leprosy patients. Abstract: Leprosy type 1 reaction (T1R) is a cell-mediated inflammatory reaction which involves skin and peripheral nerves in leprosy. Lesions with T1R have higher production of IL-17 cytokine from CD4 + T cells along with lower TGF-β producing FOXP3 + CD4 + Tregs. IL-21 is an important cytokine that promotes the development and stability of Th17 cells in an autocrine manner. It can play an important role in the pathogenesis of T1R in leprosy. However, the mechanism by which IL-21 influences the pathogenic progress of leprosy T1R remains poorly understood. In the present study, we evaluated the expression of IL-21 cytokine in skin lesions of both non-reactional (NR) and T1R via immuno-histochemistry and quantitative PCR (qPCR). Further, expression of various genes ( IL-17A, IL-17F, TGF-β, FOXP3, RORC and IL-21 ) was also measured by qPCR in cultured cells. We also analyzed the secretion of various cytokines such as of IL-21, IL-17A/F and TGF-β in the culture supernatants by ELISA. In addition, differentiation of Th17 and Treg cells were studied in PBMC cultures after stimulation with Mycobacterium leprae sonicated antigens and rIL-21 for 48 hrs and the phenotypes of Th17 and Tregs were determined by flowcytometric analysis. Our results clearly indicate that IL-21 + T cells were significantly higher in both peripheral blood and skin lesions of T1R as compared to NR patients. Moreover, we observed that recombinant IL-21 cytokine inhibited TGF-β producing Treg cells differentiation along with up-regulating Th17 cells under in-vitro conditions. The gene expression of IL-21 was significantly negatively correlated with Treg and positively correlated with Th17 cell markers in T1R patients. Our results suggested that IL-21 promotes T1R mediated inflammation via modulating the balance of Th17 and Treg cell populations.